Effect of Total Saponins of Panax Notoginseng on Lipids Deposition of Apolipoprotein E-Knockout Mice - Changgeng FU; Ruina BAI; Yue LIU; Linzi LONG; Keji CHEN (康复学报)
Objective:To study the effect of total saponins of panax notoginseng (PNS) on high-fat diet induced lipids deposition on the aortic tissue of apolipoprotein E-knockout (ApoE-/-) mice.Methods:The atherosclerosis models were prepared with a high-fat diet in the ApoE-/-mouse model for 12 weeks. All ApoE-/-mice were randomly divided into three groups (model group, simvastatin group and total saponins group),and the wild type C57BL/6J mice were taked as the control group. ApoE-/-mice continuely intook high fat feeding by gavage for 8 weeks. Blood and the aortic root tissue were collected and serum lipid level was detected by biochemical analyzer, the serum IL-1β,IL-10 concentration was detected by ELISA, the lipid deposition of aortic tissue was observed by oil red O staining, CD68+macrophage aggregation of aortic tissue was observed by immunohistochemical staining.Results:In the model group, TC and LDL-C were significantly increased, HDL-C was slightly reduced, and IL-1β,IL-10 were also increased significantly (P<0.05).Aortic tissue oil red O positive staining cells increased significantly (P<0.05),plaque lipid deposition was evident. The dots or patches protrude into the vascular and the vascular cavity was markedly narrowed, CD68+macrophage was also increased significantly in aortic tissue (all P<0.05).Compared to the model group, TC, LDL-C and IL-1β,IL-10 were significantly reduced (P<0.05),HDL-C was slightly increased in both the simvastatin group and the total saponins group (P<0.05).Positive staining cells of oil red O in aortic tissue, were significantly reduced, plaque lipid deposition and the area decreased. The degree of convexity was significantly reduced. CD68+macrophage number and the macrophage aggregation were significantly reduced (all P<0.05).Conclusion:PNS can regulate blood lipids, inhibit the immune inflammatory response, inhibit the lipid deposition of aortainhibiting and macrophage aggregation, which might be one of the anti-atherosclerosis mechanisms.